Measuring psychological flexibility and cognitive defusion in individuals with acquired brain injury. (24th August 2021) - Rauwenhoff, Johanne; Peeters, Frenk; Bol, Yvonne; Van Heugten, Caroline
ABSTRACT: Purpose: Acceptance and Commitment Therapy (ACT) is used increasingly for individuals with psychological distress following acquired brain injury (ABI) in different countries. However, questionnaires measuring ACT-processes are often not validated for this patient group and need cross-cultural validation. This study investigated the psychometric properties of the Acceptance and Action Questionnaire for Acquired Brain Injury (AAQ-ABI; measuring psychological flexibility related to thoughts and feelings about ABI) and the Cognitive Fusion Questionnaire (CFQ-7; measuring cognitive defusion). Materials and methods: Score distribution, reliability, and convergent validity of the AAQ-ABI and the CFQ-7 were examined in Dutch individuals with ABI. Results: Seventy-three patients with ABI were included. The AAQ-ABI showed good reliability (Cronbach's α = 0.87) and the CFQ-7 excellent reliability (Cronbach's α = 0.97). Both did not show a floor or ceiling effect, nor a skewed distribution. There were strong to moderate correlations between the questionnaires and measures of psychological flexibility, mood, quality of life, and value-driven behavior (AAQ-ABI: r = −0.70–0.81; CFQ-7 = −0.67–0.84). Inter-item total correlations indicate that the questions within each questionnaire measured the same construct (AAQ-ABI: r = 0.40–0.78; CFQ-7: r = 0.84–0.93). Conclusions: The current study shows that the Dutch AAQ-ABI and CFQ-7 have acceptable to good psychometric properties when measuring psychological flexibility and cognitive defusion in patients with ABI.